PENGARUH SEDIMENTASI TERHADAP DAYADUKUNG WADUK DURIANGKANG DI PULAU BATAM - Hariyadi, Rosyid (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Duriangkang Reservoir including the estuary resevoir is built by makingresevoir at the estuary of Duriangkang River. The main function ofDuriangkang Reservoir is the raw water resources to support 78 % ofdrinking wate supply needs on Batam Island. One of several problem ofDuriangkang eservoir is erosion as a result of land clearing and building ofland at Duriangkang Catchment area. Based on the research,sedimentation rate at Duriangkang Catchment area system is as themayor sources that potentially influence the carrying capacity ofDuriangkang Reservoir.In this study, an influence to carrying capacity ofDuriangkang Reservoir is conducted toward sedimentation rate atDuriangkang Reservoir by measuring the water column depth ofDuriangkang Reservoir.